2010
DOI: 10.1109/jsen.2009.2035732
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Individual Device for Exhaled Breath Temperature Measurement

Abstract: Different thermometers have been constructed over the decades to measure the temperature of the body to help detect and monitor morbid states. They yield slightly different estimates of the core body temperature depending on the proximity of the measurement site to the internal milieu of the organism, the principle of temperature assessment, and the specific characteristics of the gauging devices. Evaluation of the exhaled breath temperature (EBT) has been recently suggested as a new method to detect inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Several research teams have investigated the assumption that inflammation of the airways would influence the temperature of the air coming from the alveoli of the lungs and that this added signal could be picked by appropriate means. [47][48][49] In previous experiments it was demonstrated that in asthmatic adults and children there was correlation between the temperature of the exhaled breath and the bronchial blood flow, the FeNO levels, and the number of sputum eosinophils. 50,51 Although the first experiments were made in sealed chambers with sophisticated equipment requiring extensive training of the patients to take the measurements, a specially designed, handheld instrument was built that allowed measurements to be taken in regular indoor environments without special requirements from the tested patients.…”
Section: Exhaled Breath Temperaturementioning
confidence: 99%
“…Several research teams have investigated the assumption that inflammation of the airways would influence the temperature of the air coming from the alveoli of the lungs and that this added signal could be picked by appropriate means. [47][48][49] In previous experiments it was demonstrated that in asthmatic adults and children there was correlation between the temperature of the exhaled breath and the bronchial blood flow, the FeNO levels, and the number of sputum eosinophils. 50,51 Although the first experiments were made in sealed chambers with sophisticated equipment requiring extensive training of the patients to take the measurements, a specially designed, handheld instrument was built that allowed measurements to be taken in regular indoor environments without special requirements from the tested patients.…”
Section: Exhaled Breath Temperaturementioning
confidence: 99%
“…Tidal‐breathing EBT was measured by means of a portable device (X‐halo breath thermometer, Delmedica Investments, Singapore) validated and fully described elsewhere . This technique allows the subject's exhaled air to pass into a thermally isolated chamber across an inflow valve, then into a copper tube with a thermal sensor, while outflow valves discard the excess air at every exhalation.…”
Section: Methodsmentioning
confidence: 99%
“…The physiological parameters of heat, humidity and CO 2 production and O 2 consumption calculated by Eqs. (3)(4)(5)(6) are in Table 2.…”
Section: Physiological Parametersmentioning
confidence: 99%
“…Popov et al [4,6] adopted a resistive thermometer to measure EBT. The advantages of this resistive sensing element are reliability and accuracy.…”
Section: Physiological Parametersmentioning
confidence: 99%
See 1 more Smart Citation